2023
DOI: 10.3389/fnut.2023.1139698
|View full text |Cite
|
Sign up to set email alerts
|

UV-B radiation enhances isoflavone accumulation and antioxidant capacity of soybean calluses

Abstract: Isoflavones are a class of flavonoids that belong to a large family of polyphenols and synthesized predominantly in legume, and they play important roles including acting as antioxidant, preventing osteoporosis, reducing the risk of atherosclerosis, and protecting against cardiovascular disease. This study focused on the accumulation and synthetic metabolism of isoflavone in soybean hypocotyl and cotyledon calluses under UV-B radiation. The results showed that UV-B radiation significantly up-regulated the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…6). Similar results were reported in soybean (33) and barley (24) sprouts. Under stress, plants experience an overabundance of ROS, leading to oxidative harm and the initiation of antioxidative protection mechanisms.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…6). Similar results were reported in soybean (33) and barley (24) sprouts. Under stress, plants experience an overabundance of ROS, leading to oxidative harm and the initiation of antioxidative protection mechanisms.…”
Section: Discussionsupporting
confidence: 89%
“…Our study demonstrated that the exogenous MT significantly reduces the accumulation of H 2 O 2 and MDA under MeJA treatment ( Figures 3A – C , p < 0.05), enhances the ability to scavenge DPPH and ABTS free radicals ( Figures 4E , F , p < 0.05), as well as the fluorescence intensity of H 2 O 2 , and ( Figure 6 ). Similar results were reported in soybean ( 33 ) and barley ( 24 ) sprouts. Under stress, plants experience an overabundance of ROS, leading to oxidative harm and the initiation of antioxidative protection mechanisms.…”
Section: Discussionsupporting
confidence: 88%
“…The antioxidation property of flavonoids has been evidenced in many other reports. 26,27 Due to the high content level of flavonoids accumulated in the seeds of BLK, we speculated that those antioxidants might help to combat environmental stress during germination. There was no significant germination difference between BLK and YL seeds when they were imbibed in distilled water, implying that the developmental program of seeds was not affected in the BLK.…”
Section: ■ Resultsmentioning
confidence: 99%